2014
DOI: 10.1186/1471-2415-14-84
|View full text |Cite
|
Sign up to set email alerts
|

Influence of uncorrected refractive error and unmet refractive error on visual impairment in a Brazilian population

Abstract: BackgroundThe World Health Organization (WHO) definitions of blindness and visual impairment are widely based on best-corrected visual acuity excluding uncorrected refractive errors (URE) as a visual impairment cause. Recently, URE was included as a cause of visual impairment, thus emphasizing the burden of visual impairment due to refractive error (RE) worldwide is substantially higher. The purpose of the present study is to determine the reversal of visual impairment and blindness in the population correctin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
0
11
0
3
Order By: Relevance
“…In contrast, Nirmalan et al [ 32 ] and Emamian et al [ 33 ] reported that men were more likely to have received eye care services in hospitals in rural India and Northern Iran. Furthermore, a sex difference in the prevalence of visual impairment has been noted in both high-income and low-income countries [ 34 35 36 37 ]. The main cause of this disparity is that, in low-income countries, women use eye care services much less frequently [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Nirmalan et al [ 32 ] and Emamian et al [ 33 ] reported that men were more likely to have received eye care services in hospitals in rural India and Northern Iran. Furthermore, a sex difference in the prevalence of visual impairment has been noted in both high-income and low-income countries [ 34 35 36 37 ]. The main cause of this disparity is that, in low-income countries, women use eye care services much less frequently [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, myopia was estimated to affect 108 million people globally (Kandel et al, 2018;Stone & Shea, 2019). According to the 2010 Global Burden of Disease Study, approximately 1893 million people suffered from myopia worldwide in 2016 (Grzybowski, Kanclerz, & Muzyka-wo, 2019) Moreover, this number is estimated to increase to 4949 million by 2050, and the majority of these individuals will likely come from low-and middleincome countries (Ferraz, Corrente, Opromolla, & Schellini, 2014;Phec, 2017). Unfortunately, to date, no treatments are available to cure myopia or alter its progressive course unless a proper correction is given at the right time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in China, it has been seen that there is a moderately high occurrence of astigmatism among ages of 3–6 years ( 10 ). In Sao Paulo, uncorrected refractive error was found to cause blindness and low vision which, however, were reversible in 4.8% and 1.6% respectively among the Brazilian population ( 11 ).…”
Section: Introductionmentioning
confidence: 99%